Neutrophils unveiled in chronic lymphocytic leukemia - McManus, Sheighlah; Khare, Priyanka; Bertilaccio, Maria Teresa S. (Frontiers in Immunology, 2025)
This review explores neutrophils’ roles in chronic lymphocytic leukemia (CLL), highlighting their functions within the immune system. While neutrophils are known for fighting infections, their altered behavior in CLL significantly impacts disease progression. This review notes the reduced phagocytic abilities of neutrophils and the increased formation of neutrophil extracellular traps (NETs) in patients with CLL. It also examines the effects of CLL treatments, including chemotherapy, immunotherapy and targeted therapies, on neutrophils’ count and function, stressing the need for improved strategies to manage therapy-induced immune dysfunction. This review also provides detailed information about the interactions between neutrophils and other immune elements in CLL microenvironment, providing insights for developing therapeutic approaches that can restore immune function and improve patients’ quality of life.